Phasenstabilisierung und Oberflächenaktivierung von Sauerstoffseparationsmembranen aus dotiertem Ba$_{0,5}$Sr$_{0,5}$Co$_{0,8}$Fe$_{0,2}$O$_{3-?}$ - Unger, Lana-Simone (Schriften des Instituts für Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Angewandte Materialien - Werkstoffe der Elektrotechnik, 2019)
Ba$_{0,5}$Sr$_{0,5}$Co$_{0,8}$Fe$_{0,2}$O$_{3-?}$ (BSCF) is the most promising material für energy efficient oxygen separation membranes. But its electrical and transport properties are unstable at temperatures below 840 °C. Reasons are structural changes to secondary phases in the cubic lattice. By doping with Y, Ti and Nb the cubic lattice shall be stabilized. Goal of this work are analyses of the dopant's influences on BSCF's electrochemical properties.